STUDI DESKRIPTIF PELAKSANAAN PEMBELAJARAN DARING PADA KELAS RENDAH DI SEKOLAH DASAR NEGERI 04 SELUMA - Triaji Prasetio; Sri Dadi (JURIDIKDAS, 2022)
This study aims to describe the process of implementation online learning in 1st, 2 nd, and 3 rd  grades at SD Negeri 04 Seluma and the supporting and inhibiting factors. This research was a qualitative research with the phenomenological approach. The research subjects in this study were 1st , 2 nd, and 3 rd grade teachers and 1 st, 2 nd, and 3 rd graders. The research instrument was the researcher himself using observation sheets, interviews, questionnaires, and documentation. The data analysis techniques data collection, data condensation, data presentation, and drawing conclusions. Techniques for validating data through extended observations, increasing persistence, as well as triangulation of sources and techniques. The results showed that the implementation of online learning in the 1 st, 2 nd, and 3 rd  grades consisted of  preliminary activities, core activities, and closing activities. There are supporting factors for online learning, namely the availability of online learning support facilities in schools such as laptops and gadgets, the state internet network, the provision of internet quota from the Ministry of Education and Culture, and adequate textbooks. In addition, it was also found that the inhibiting factors for online learning were the lack of supervision of parents and teachers during online learning, the level of understanding of students was different, teachers were not fully ready to carry out online learning, not all students had devices for online learning. Based on the results of the study, it can be concluded that online learning at the 04 Seluma State Elementary School has been carried out in the lower class.